(untitled) (Bangladesh Journal of Microbiology, 2019)
Fermented and non-fermented Khmer rice noodles is produced basically from indica rice, a popular food item and most important nutrition sources along with an integral part of rural household’s food security of Cambodian population. This study was done to evaluate the microbiological quality of fermented and non-fermented Khmer rice noodle samples sold throughout the country. In total, 75 Khmer rice noodle samples, (23 fermented and 52 nonfermented) were collected from five local varieties (Nom-Banhchok, Nom-Banhhoy, Koyteavkat, Lotchhar and Koyteav) and three locations (Kandal province, Siem Reap province and Phnom Penh city) of Cambodia. The study results showed that irrespective of sample location, all the fermented and non-fermented rice noodle samples analyzed were either contaminated with faecal origin bacteria (Enterococcus spp., and coliform), or faecal indicator bacteria including Escherichia coli and pathogenic bacteria including, Staphylococcus spp., and Bacillus spp. Of the fermented rice noodles about 74% and 98% of non-fermented rice noodles was found contaminated with all the above mentioned bacteria. In addition, 30% samples were found contaminated with Klebsiella pneumonia spp. Furthermore, among the Staphylococcus aureus isolates, three isolates TM-K5-3, OM-L4 and DM-KK3-2 was seen producing protein A (aggregated polysaccharide specific immune latex strongly), positive clumping factor production and harbored type six coagulase gene and among the B. cereus strains, 12 B. cereus, isolates was seen produced enterotoxin, which may cause severe diarrhea and one B. cereus (DM-NB1) isolate was found harbored CRS gene, which may produce emetic toxin, unsafe for human consumption. Therefore, strong regulatory monitoring should be established in order to improve the quality of food to ensure public health. Bangladesh J Microbiol, Volume 35 Number 2 December 2018, pp 82-88